The effect of motivational interview persons with diabetes on self-management and metabolic variables. - Dogru, Ayse; Ovayolu, Nimet; Ovayolu, Ozlem (My University, 2019)
To evaluate the effect of motivational interviewing on diabetics related to perceived self-management and metabolic variables.The randomised controlled and experimental study was conducted at a public hospital located in the city of Gaziantep in Turkey and comprised diabetes patients attending the outpatient clinic of endocrinology and metabolic diseases from April to July 2015. The subjects were randomised into two equal intervention and control groups. Four motivational interviewing sessions, each of which took about 15-20 minutes, were conducted by a nurse to the intervention group. Data was collected using a questionnaire and the Perceived Diabetes Self-Management Scale.Of the 60 subjects, there were 30 (50%) in ach of the two groups. The perceived self-management perception mean score of the intervention group was 17.1 } 5.6 at baseline and increased to 35.0 } 4.1 postintervention (p<0.05). Mean scores of body mass index, fasting and postprandial blood glucose, glycated haemoglobin, cholesterol, triglyceride, low density lipoprotein cholesterol and systolic and diastolic blood pressures of subjects in the intervention group decreased after the intervention, and their high density lipoprotein cholesterol mean scores increased (p<0.05).Motivational interviewing technique positively affected the metabolic control indicators of the diabetes patients and increased their perceived self-management.
Keywords: Adult; Blood Glucose; Glycated Hemoglobin; Male; Turkey; Self-Management; Cholesterol, HDL; Blood Pressure; Cholesterol, LDL; Fasting; Motivational Interviewing; Middle Aged; Postprandial Period; Cholesterol; Diabetes Mellitus, Type 2; Humans; Female; Triglycerides; Aged; 3. Good health